2004
DOI: 10.1068/p5285
|View full text |Cite
|
Sign up to set email alerts
|

Shape-from-Shading Depends on Visual, Gravitational, and Body-Orientation Cues

Abstract: The perception of shading-defined form results from an interaction between shading cues and the frames of reference within which those cues are interpreted. In the absence of a clear source of illumination, the definition of 'up' becomes critical to deducing the perceived shape from a particular pattern of shading. In our experiments, twelve subjects adjusted the orientation of a planar disc painted with a linear luminance gradient from one side to the other, until the disc appeared maximally convex-that is, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 16 publications
10
36
0
Order By: Relevance
“…Studies that used complex illuminated objects with strong lighting direction cues concluded that lighting cues guide shape-from-shading (6, 7), whereas studies that used weaker lighting cues concluded that they have little effect (8)(9)(10)(11)(12). We discuss the lighting cues in previous studies in further detail in SI Discussion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that used complex illuminated objects with strong lighting direction cues concluded that lighting cues guide shape-from-shading (6, 7), whereas studies that used weaker lighting cues concluded that they have little effect (8)(9)(10)(11)(12). We discuss the lighting cues in previous studies in further detail in SI Discussion.…”
Section: Resultsmentioning
confidence: 99%
“…The weight ratio w prior /w cue determines whether the prior or the cues have a greater influence on the effective lighting direction. This model is well established in the literature on the subjective vertical (11,17). We have recently shown that it is largely equivalent to a Bayesian cue combination model that assigns reliability weights to noisy directional cues [here the prior, which we treat as just another cue (18,19), and the lighting cues] and combines the cues by making a maximum-likelihood direction estimate (16).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A leftward bias has also been observed for the assumed direction of illumination in shaded images (Howard et al 1990) (Jenkin et al 2003;Jenkin et al 2004;McManus et al 2004), and it has been demonstrated that this leftward bias persists when tilted in the roll plane (Barnett-Cowan et al 2013;Jenkin et al 2003). Likewise, leftward biases were reported for spatial perception of the body (Barnett- Cowan et al 2013;Barnett-Cowan and Harris 2008;Tarnutzer et al 2012), perceived direction of gravity (Schuler et al 2010), and the perceptual upright (Dyde et al 2006).…”
Section: Discussionmentioning
confidence: 79%